2015
DOI: 10.1073/pnas.1506207112
|View full text |Cite
|
Sign up to set email alerts
|

Precision-guided antimicrobial peptide as a targeted modulator of human microbial ecology

Abstract: One major challenge to studying human microbiome and its associated diseases is the lack of effective tools to achieve targeted modulation of individual species and study its ecological function within multispecies communities. Here, we show that C16G2, a specifically targeted antimicrobial peptide, was able to selectively kill cariogenic pathogen Streptococcus mutans with high efficacy within a human saliva-derived in vitro oral multispecies community. Importantly, a significant shift in the overall microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
134
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 37 publications
0
134
0
Order By: Relevance
“…C16G2 had antimicrobial mechanisms similar to traditional AMPs, and critically, its membrane-disrupting activity specifically targets S. mutans from multispecies biofilms without affecting closely related non-cariogenic oral streptococci [Eckert et al, 2006;Kaplan et al, 2011]. More recently, an in vitro study on human saliva-derived polymicrobial biofilms was able to demonstrate that treatment with C16G2 not only eliminated S. mutans, but also resulted in a more benign oral microbial community with increased populations of health-associated bacteria and fewer harmful Gram-negative bacteria [Guo et al, 2015]. C16G2 is recognized by the US Food and Drug Administration as an investigational new drug for dental caries prevention and has successfully completed phase II clinical trials, where it was delivered to patients in the form of a dental gel loaded in trays.…”
Section: Ecological Approaches To Caries Preventionmentioning
confidence: 99%
“…C16G2 had antimicrobial mechanisms similar to traditional AMPs, and critically, its membrane-disrupting activity specifically targets S. mutans from multispecies biofilms without affecting closely related non-cariogenic oral streptococci [Eckert et al, 2006;Kaplan et al, 2011]. More recently, an in vitro study on human saliva-derived polymicrobial biofilms was able to demonstrate that treatment with C16G2 not only eliminated S. mutans, but also resulted in a more benign oral microbial community with increased populations of health-associated bacteria and fewer harmful Gram-negative bacteria [Guo et al, 2015]. C16G2 is recognized by the US Food and Drug Administration as an investigational new drug for dental caries prevention and has successfully completed phase II clinical trials, where it was delivered to patients in the form of a dental gel loaded in trays.…”
Section: Ecological Approaches To Caries Preventionmentioning
confidence: 99%
“…In particular, it kills an oral cariogenic Streptococcus mutans within a biofilm formed by three bacterial species, without affecting other closely related noncariogenic oral Streptococci [63]. Guo et al [64] reported that C16G2 effectively and selectively killed S. mutans within a microbiota community from human saliva. After C16G2 treatment, there was significantly reduced abundance of several bacterial species, which are metabolically dependent or physically interactive with S. mutans.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…The feasibility of this approach has been demonstrated by the development of C16G2, a STAMP specifically targeting S.mutans, the bacterium known to cause dental caries. C16G2 has been shown to remove S. mutans within in vitro multi-species biofilms with high efficacy and specificity, 68,70 and is under further animal and human evaluations. 71 The successful demonstration of this targeted approach could serve as proof-of-concept for applying this technology to the treatment of denture-related Candida infections.…”
Section: 53mentioning
confidence: 99%